Genome Report: Whole Genome Sequence and Annotation of the Parasitoid Jewel Wasp Nasonia giraulti Laboratory Strain RV2X[u]. Issue 8 (1st August 2020) - Wang, Xiaozhu; Kelkar, Yogeshwar D; Xiong, Xiao; Martinson, Ellen O; Lynch, Jeremy; Zhang, Chao; Werren, John H; Wang, Xu
Abstract: Jewel wasps in the genus of Nasonia are parasitoids with haplodiploidy sex determination, rapid development and are easy to culture in the laboratory. They are excellent models for insect genetics, genomics, epigenetics, development, and evolution. Nasonia vitripennis ( Nv ) and N. giraulti ( Ng ) are closely-related species that can be intercrossed, particularly after removal of the intracellular bacterium Wolbachia, which serve as a powerful tool to map and positionally clone morphological, behavioral, expression and methylation phenotypes. The Nv reference genome was assembled using Sanger, PacBio and Nanopore approaches and annotated with extensive RNA-seq data. In contrast, Ng genome is only available through low coverage resequencing. Therefore, de novo Ng assembly is in urgent need to advance this system. In this study, we report a high-quality Ng assembly using 10X Genomics linked-reads with 670X sequencing depth. The current assembly has a genome size of 259, 040, 977 bp in 3, 160 scaffolds with 38.05% G-C and a 98.6% BUSCO completeness score. 97% of the RNA reads are perfectly aligned to the genome, indicating high quality in contiguity and completeness. A total of 14, 777 genes are annotated in the Ng genome, and 72% of the annotated genes have a one-to-one ortholog in the Nv genome. We reported 5 million Ng-Nv SNPs which will facility mapping and population genomic studies in Nasonia . In addition, 42 Ng -specific genes were identified by comparing with Nv genome and annotation. This is the first de novo assembly for this important species in the Nasonia model system, providing a useful new genomic toolkit.